LEKA Lexical Knowledge Achieve Terminology in Social Sciences - Noria, Tugang; Bromeley, Philip; Amee, Joan (UNIMAS Publisher, Universiti Malaysia Sarawak, 2020)
The LEKA (Lexical Knowledge Archive) Project involves language modernization and modification through word formation/coinage, word blending and word borrowing which focuses on developing specialised terminology for Social sciences and Humanities in the Iban language. This may look like an ordinary wordlist, a form of bilingual archive of specialised terminology in Social Sciences and Humanities, but for the authors this is our labour of love. Years of research is finally manifested into a publication with hopes to further modernize the Iban language to elevate its function into becoming an academic language. Leka in Iban literally means a seed of fruits or vegetables or a seed of word, hence the term LEKA aptly represents this initiative.